2021
DOI: 10.1080/2090598x.2021.1876289
|View full text |Cite
|
Sign up to set email alerts
|

The association between sarcopenia and bladder cancer-specific mortality and all-cause mortality after radical cystectomy: A systematic review and meta-analysis

Abstract: Objective: To compare cancer-specific mortality (CSM) and all-cause mortality (ACM) between patients with and without sarcopenia who underwent radical cystectomy for bladder cancer. Materials and methods: We performed a systematic review and meta-analysis of original articles published from October 2010 to March 2019 evaluating the effect of sarcopenia on CSM and ACM. We extracted hazard ratios (HRs) and 95% confidence intervals (CIs) for CSM and ACM from the included studies. Heterogeneity amongst studies was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…The findings are similar to previous meta-analysis and systematic reviews that attempted to understand the association of sarcopenia, in subjects with bladder cancer undergoing RC, with clinical and prognostic outcomes. For instance, the review by Ibilibor et al 16 included 5 studies with around 1400 subjects and found that cancer-specific (HR 1.64) as well as all-cause mortality (HR 1.41) increased in those with sarcopenia, compared to non-sarcopenic individuals. Another narrative review by Ahmadi et al 41 included five studies and reported that psoas muscle mass has been shown by studies to predict adverse outcomes following RC, including complication rate and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings are similar to previous meta-analysis and systematic reviews that attempted to understand the association of sarcopenia, in subjects with bladder cancer undergoing RC, with clinical and prognostic outcomes. For instance, the review by Ibilibor et al 16 included 5 studies with around 1400 subjects and found that cancer-specific (HR 1.64) as well as all-cause mortality (HR 1.41) increased in those with sarcopenia, compared to non-sarcopenic individuals. Another narrative review by Ahmadi et al 41 included five studies and reported that psoas muscle mass has been shown by studies to predict adverse outcomes following RC, including complication rate and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] We conducted this meta-analysis to provide evidence on the association of sarcopenia, among patients with bladder cancer undergoing radical cystectomy, with the risk of mortality and complications. Our study aims to build upon the previous meta-analysis on this issue by Ibilibor et al, 16 with the intent to update the existing evidence for informing clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the risks differed for various patient groups in terms of survival, death rates, and other unfavorable outcomes. Patients who had emergency laparotomies had the highest all-cause mortality ( 52 ), whereas those who underwent radical cystectomies had the lowest ( 51 ). These differences may be largely due to the different definitions of sarcopenia used and may also be influenced by different measurement methods for muscle mass, strength, and function.…”
Section: Discussionmentioning
confidence: 99%
“…With these prerogatives, the cancer microenvironment enriched by cytokines, transcription factors, and infiltrating immune cells, could be able to enhance both the tumor’s growth and its immune escape ability [ 14 ]. Such a scenario might exacerbate a catabolic condition induced by the primary BC itself potentially leading to cancer development and progression by promoting tumoral cachexia, which has been proven to be a risk factor for poorer perioperative recovery [ 15 , 16 ]. Thus, the host’s anabolism and immune competence could be impaired and serum marker alterations might mirror such an imbalance.…”
Section: Introductionmentioning
confidence: 99%